2015
DOI: 10.1016/j.bbmt.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graft Source on Unrelated Donor Hemopoietic Stem Cell Transplantation in Adults with Acute Myeloid Leukemia after Reduced-Intensity or Nonmyeloablative Conditioning: A Study from the Société Francaise de Greffe de Moelle et de Thérapie Cellulaire

Abstract: This retrospective report compared the 4-year outcomes of allogeneic stem cell transplantation (allo-SCT) in 651 adult patients with acute myeloid leukemia receiving a reduced-intensity (RIC) or nonmyeloablative conditioning (NMA) regimen according to the type of unrelated donors. These were either umbilical cord blood (UCB, n = 205), a 9/10 mismatched unrelated donor (MisMUD, n = 99), or a 10/10 matched unrelated donor (MUD, n = 347) graft. Neutrophil recovery was slower in UCB (74.5% by day 42) compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In addition, several recent studies demonstrated highly similar survival results between CBT and MSD recipients [12][13][14]27,45,46]. However, in this study, the rate of OS after CBT was significantly inferior to that after BMT or PBSCT from MSDs.…”
Section: Discussionsupporting
confidence: 40%
“…In addition, several recent studies demonstrated highly similar survival results between CBT and MSD recipients [12][13][14]27,45,46]. However, in this study, the rate of OS after CBT was significantly inferior to that after BMT or PBSCT from MSDs.…”
Section: Discussionsupporting
confidence: 40%
“…In a world where most retrospective studies show similar outcomes between MUD, misMUD, and CB, as in the Malard et al study [5], and now add haplo-identical donors, how do these data help us move the alternative donor transplantation field forward? Although there is no single answer Biology of Blood and Marrow Transplantation j o u r n a l h o m e p a g e : w w w .…”
mentioning
confidence: 93%
“…In this issue of Biology of Blood and Marrow Transplantation, Malard et al reported on the outcomes of CB compared with MUD and misMUD after reduced-intensity or nonmyeloablative conditioning [5]. Although we could be tempted to dissect differences in patient populations to explain their effect, or lack thereof, on the results, the message would not change.…”
mentioning
confidence: 93%
See 2 more Smart Citations